Analysis of injury mechanism and thoracic response of elderly, small female PMHS in near-side impact scenarios - Bolte, John; Fibbi, Clare; Tesny, Angela C.; Kang, Yun-Seok; Agnew, Amanda M.; Shurtz, Benjamin K.; Pipkorn, Bengt; Rhule, Heather; Moorhouse, Kevin (Traffic injury prevention, 2023)
In 2020, 17% of all crash fatalities were individuals aged 65 years or older. Crash data also revealed that for older occupants, thoracic related injuries are among the leading causes of fatality. Historically, the majority of near-side impact postmortem human subjects (PMHS) studies used a generic load wall to capture external loads that were applied to PMHS. While these data were helpful in documenting biofidelity, they did not represent a realistic response an occupant would undergo in a near-side crash. The objective of this research was to test small, elderly female PMHS in a repeatable, realistic near-side impact crash scenario to investigate current injury criteria as they relate to this vulnerable population. Ten small, elderly PMHS were subjected to a realistic near-side impact loading condition. The PMHS were targeted to be elderly females age 60+, approximately 5 th percentile in height and weight, with osteopenic areal bone mineral density. Each subject was seated on a mass-production seat, equipped with a side airbag and standard three-point restraint with a pretensioner. Other boundary conditions included an intruding driver's side door. PMHS instrumentation included strain gages on ribs 3-10 bilaterally to identify fracture timing. Two chestbands were used to measure chest deflection, one at the level of the axilla and one at the level of the xiphoid process. Injuries observed included rib fractures, particularly on the struck side, and in multiple cases a flail chest was observed. Eight of ten subjects resulted in AIS3+ thoracic injuries, despite previously tested ATDs predicting less than a 10% chance of AIS3+ injury. Subjects crossed the threshold for AIS3 injury in the range of only 1% − 9% chest compression. Additionally, mechanisms of injury varied, as some injuries were incurred by door interactions while others came during airbag interactions. This research points to two areas of concern that likely require further analysis: (1) the appropriateness of potentially oversimplified PMHS testing to establish injury thresholds and define injury criteria for complicated crash scenarios; (2) the importance of identifying the precise timing of injuries to better understand the effect of current passive restraint systems.